Erosion and sedimentation analysis as basic reference for land conservation planning on Lesti Sub-Watershed - Sumanto, Hari; Dermawan, Very; Asmaranto, Runi (Fakultas Teknik Universitas Brawijaya, 2023)
The Lesti sub-watershed area is mostly steep mountain slopes, when the rain fall it carries erosion and sediment material. Erosion Hazard Level on Lesti Sub-Watershed were obtained as follows: Class I 11.92%; Class II 27.45%; Class III 43.85%; Class IV 13.06%; Class V 3.99%. Four (4) parameters overlaid to determine the land criticality level are: the map of land coverage, land slope, erosion risk level, and management aspect. Generally, Lesti Sub-Watershed is categorized as: very critical 0.14%; critical 4.61%; a rather critical 28.06%; critical potential 53.66%; and normal 13.51%. From SWAT analysis with total sub-basin of 39 and 1013 HRU (Hydrology Respon Unit) resulted the average value respectively soil erosion is 119.60 tons/ha/year; sediment yields 310.77 tons/ha/year; rainfall 2143.27 mm/year; and surface runoff 1120.65 mm/year. The suggestions of the watershed area conservancy requires a vegetative (planting) and mechanical (building) method. The vegetative method such as: alleys cropping; reforestation; agroforestry; relay cropping; soil cover cropping as natural green manure; living fence or windbreak; mixed cropping farm; mulch; environment greening; strip cropping with 20.65% effectivity; and filter strip with 26.03% effectivity. The mechanical method such as: contour tillage with 29.71% effectivity; terracing with 23.41% effectivity; check dam with 17.50% effectivity; and mound.